Systematic screening of isogenic cancer cells identifies DUSP6 as context-specific synthetic lethal target in melanoma - Wittig-Blaich, Stephanie; Wittig, Rainer; Schmidt, Steffen; Lyer, Stefan; Bewerunge-Hudler, Melanie; Gronert-Sum, Sabine; Strobel-Freidekind, Olga; Muller, Carolin; List, Markus; Jaskot, Aleksandra; Christiansen, Helle; Hafner, Mathias; et al. (Oncotarget, 2017)
Next-generation sequencing has dramatically increased genome-wide profiling options and conceptually initiates the possibility for personalized cancer therapy. State-of-the-art sequencing studies yield large candidate gene sets comprising dozens or hundreds of mutated genes. However, few technologies are available for the systematic downstream evaluation of these results to identify novel starting points of future cancer therapies.We improved and extended a site-specific recombination-based system for systematic analysis of the individual functions of a large number of candidate genes. This was facilitated by a novel system for the construction of isogenic constitutive and inducible gain- and loss-of-function cell lines. Additionally, we demonstrate the construction of isogenic cell lines with combinations of the traits for advanced functional in vitro analyses. In a proof-of-concept experiment, a library of 108 isogenic melanoma cell lines was constructed and 8 genes were identified that significantly reduced viability in a discovery screen and in an independent validation screen. Here, we demonstrate the broad applicability of this recombination-based method and we proved its potential to identify new drug targets via the identification of the tumor suppressor DUSP6 as potential synthetic lethal target in melanoma cell lines with BRAF V600E mutations and high DUSP6 expression.
EVALuna2:57246